Evaluation of Seed and Seedling Quality of Azadirachta indica A. Juss. (Neem) Seeds Collected from Various Agro-Ecological Regions of Gujarat State - Mishra, Dhruv Kumar; Kumar, Devendra (Indian Forester, 2017)
Neem (Azadirachta indica A. Juss) seeds were collected for evaluation of seeds and seedling qualities of grown in various agro-ecological regions (AERs) which is extensively planted in AER-1, AER-4 and AER-5 in state of Gujarat, India. Collected seeds were tested in lab for 100 seed weight, germination percentage (G%) and in nursery for G%, speed of germination in terms of mean germination time (MGT), germination value (GV) and seedling performance viz. seedling height, number of leaves, total biomass, root shoot ratio, sturdiness quotient (SQ) and vigour index. Results indicated that seed may be collected from AER 1 followed by AER 5 for significantly better seed seedling qualities.